Optimization and Kinetics Extraction of Natural Dyes from Henna Leaves (Lawsonia inermis L.) with Ultrasonic Assistance - Achmad Qodim Syafaatullah; Dwi Setyorini; Melani Ganing; Renova Panjaitan; Ni’matul Azizah (Jurnal Kimia Sains dan Aplikasi, 2023)
The Lawson dye contained in the leaves of Lawsonia inermis L. has a red-orange color, which can be used as a fabric dye. The solvent is ethanol because it can attract flavonoid compounds bound to Lawson. The ultrasonic-assisted extraction method is employed to enhance the extraction process by breaking down cell walls, thereby facilitating a more rapid extraction of the desired solute. This study investigated the effects of material-to-solvent ratio, ethanol concentration, and extraction time. The research results were analyzed using a UV-Visible spectrophotometer to determine the yield of Lawson extract. The Face-Centered Composite Design (FCCCD) method was applied to this study to obtain optimal analysis results and extraction conditions. The independent variables in this study were the ratio of ingredients to solvent (0.02-0.06 g/g), ethanol concentration (20-60%), and extraction time (5-15 minutes). The optimal extraction conditions were obtained at a ratio of 0.02 g/g, an ethanol concentration of 60%, and an extraction time of 15 minutes, with a predicted model yield of 15.417%. The actual yield under these conditions was found to be 15.4934%. Furthermore, the extraction kinetics model was analyzed to study and predict the optimal Lawson extraction results. Extraction kinetics calculations were carried out using first-order and second-order based on the Lagergren equation. The most suitable extraction kinetic model is second-order with a determinant coefficient value, or the value of R2 is 1, which indicates that the order kinetic model equation represents the actual conditions.